Analysis of Financial Feasibility and Added Value of Mangrove Plants Processed Product: A Case Study in Kampung Nipah, North Sumatra Province, Indonesia - Adisti Yulia Pradita; Agus Purwoko; Patana, Pindi (Talenta Publisher, 2022)
The mangrove ecosystem provides many benefits for the environment and ecosystem services. Mangrove economically can be utilized to become any miscellaneous food and drink. One of the potential mangrove areas is Kampung Nipah, Sei Nagalawan Village, Perbaungan District, Serdang Bedagai Regency, North Sumatra. This study aims to identify the technical aspect of product processing and to analyze the financial feasibility and the added value distribution of mangrove processed products. Data collection used the sensus method and the open interview method with the leader and members of Kelompok Tani MuaraTanjung and data analyzed using the quantitative descriptive method. The result shows that the processing product is still manual and done cooperatively. The products obtained are Jeruju chips, Pedada syrup, and Dodol Api-Api. The business of mangrove processed products produces profit and worth by financial with a Revenue Cost Ratio (R/C) value of 1.6, 1.2, and 1.2, respectively. The Payback Period is 2, 5, and 4, respectively. Break Even Point (BEP) is 15, 13, and 14, respectively. And the BEP Analysis in Rupiah is Rp 5.045, Rp 10.098, and Rp 8.001. All the results show a profit. The added value for each product is Rp 52.871/kg, Rp 20.725/kg, and Rp 31.318/kg.